Gambaran Stigma Internal dan Kecemasan Pada Individu Gay dan Kaitannya dengan Perilaku Pencarian Pengobatan - Elisabeth P Y Carvallo (Jurnal Ners, 2026)
This study aims to explore internal stigma and anxiety among gay men and their relationship to help-seeking behavior. This study employs a qualitative approach with a descriptive design. Data were collected through structured interviews with 8 gay men aged 19–53 years, selected using purposive sampling. The interview data were analyzed using thematic analysis. The findings indicate that internal stigma plays a role in generating significant anxiety among participants, which significantly impacts their behavior and decisions regarding seeking treatment. Internal stigma manifests as feelings of guilt, self-reproach, and negative self-evaluation, affecting gay men seeking treatment when they experience physical symptoms of sexually transmitted infections and when they remain closed-off and conceal their sexual identity from healthcare providers. The anxiety experienced by participants not only acts as a barrier to seeking treatment due to fear of stigma and moral judgment from healthcare providers, but also serves as a motivator to access healthcare services because the fear of greater health risks outweighs the fear of social stigma. Additionally, positive previous experiences accessing healthcare services, along with social support, can reduce anxiety, thereby making gay men more proactive in seeking treatment.